Dynamic-based pushover analysis for one-way plan-asymmetric buildings. (15th May 2018) - Rofooei, Fayaz R.; Mirjalili, M.R.
Highlights: The torsional and higher modes effects are properly considered in the proposed pushover procedure. The drifts obtained from response spectrum analysis for flexible and stiff edges is used to construct the load pattern. The load pattern includes both the lateral forces and the torsional moments. The procedure can accurately estimate the results while it is more applicable than other existing methods. Abstract: A simple Dynamic-based Pushover analysis for Plan Asymmetric buildings (DPPA) is proposed with the aim of properly considering the effects of torsional behavior as well as the higher modes in the applied lateral load pattern. According to the proposed method, the peak story drifts obtained from the response spectrum analysis (RSA) can be resolved into their translational and rotational components, and the related equivalent static lateral forces and torsional moments can be calculated. Consequently, for accurate estimation of the maximum drift demands of plan-asymmetric buildings, it is proposed that the drift responses obtained from the RSA for the stiff and flexible edges of the building be utilized to construct two lateral-torsional load patterns for nonlinear static analyses. The envelope of the results of two pushover analyses using the constructed load patterns is considered as the seismic demands of the building structure. The target displacement for the pushover analyses can be calculated using the available codes such as ASCE 41-13 with a suggested modification factor. Using a number of structural models, the versatility of the proposed DPPA procedure in estimating their seismic demands is demonstrated by comparison of the obtained results with those calculated from nonlinear time history analysis (NL-THA) and other well –known pushover procedures such as the practical modal pushover analysis (PMPA) and the extended-N2 methods. The comparison of the results clearly demonstrates the efficiency of the proposed DPPA procedure in accurately capturing the response parameters, especially in shear-building structures. Also, it is more applicable and much easier to use in practical structural designs in comparison to other available enhanced pushover procedures.